A mixed method exploration of job morale of physicians working in public healthcare settings in Kazakhstan during the COVID-19 pandemic - Alina Kuandyk; Mariya Dmitriyeva; Nazerke Toleukhanova; Maev Conneely; Timur Suleimenov; Dauren Sarssenov; Raimzhan Mamytkhan; Madiyar Sakhayev; Arman Tleubergenov; Medet Toleubayev (Journal of Health, Population and Nutrition)
Abstract Background Physicians faced increased workloads during the COVID-19 pandemic, which exposed them to considerable physical and psychological stress. Gaining insight into shapers of job morale of physicians can help healthcare administrators assess the effectiveness of current work conditions and support systems, enabling them to develop policies that improve work environments and prepare healthcare systems for future resurgences of COVID-19 and other future unknown challenges. Therefore, the present study aimed to improve the understanding of physicians’ experiences of job morale in Kazakhstan during the COVID-19 pandemic. Methods This was an explanatory sequential mixed method study that adopted an online structured questionnaire and semi-structured individual interviews as tools for data collection. The Warr-Cook-Wall scale, Maslach Burnout Inventory Human Services Survey for Medical Personnel, and Beck Depression Inventory were used to measure job morale indicators. The interview topic guide, in turn, covered two key areas: general views on physicians’ job morale during the COVID-19 pandemic and specific experiences which worsened or improved job morale during the COVID-19 pandemic. Descriptive statistics and regression models were utilised to analyse the quantitative data, while thematic analysis was employed for the qualitative data. Results A total of 2086 survey responses and 30 interviews were analysed. Although job motivation was moderate, physicians were rather satisfied with their jobs. The prevalence of burnout was 30.97%, and signs of severe depression symptoms were detected among 3.69% of participants. Four themes emerged from the thematic analysis: (1) fear of uncertainty; (2) media scrutiny; (3) resurgence in appreciation; and (4) heightened sense of duty. Conclusions Despite the significant challenges posed by the COVID-19 pandemic, physicians in Kazakhstan’s public healthcare sector maintained generally positive job morale. This was mainly due to their strong sense of calling and a renewed appreciation for their role. Future research should rigorously examine longitudinal changes in job morale and the relationship between physicians’ job morale and patient experiences.